(untitled) - French, Anthony Philip (New York, 1971)
About 109 problems with solutions and 84 worked examples help the student to grasp the essential aspects of the subject, and to develop proficiency in using the powerful methods of Newtonian Mechanics. Moreover, the problem of motion and the concept of inertial frames is faced from the very beginning, and runs through the entire development of classical mechanics. This new and fresh approach will give the student the best introduction to an important area of physics
Keywords: Cơ học,Mechanics